Study on a novel immobilized microbe pellets constructed with Alcaligenes sp. R3 and its ability to remove tetracycline - Liu, Zhuangzhuang; Yang, Yabo; Liu, Gang; Fang, Jun (Journal of environmental chemical engineering, 2023)
Microbial technology provides a feasible and effective means for removing tetracycline from water bodies. In this study, a novel tetracycline removal strain was isolated from pig manure and identified as an Alcaligenes sp. The effects of inoculation dose, initial tetracycline concentration, pH and temperature on the tetracycline removal efficiencies of the Alcaligenes sp. R3 strain were investigated. Response surface methodology (RSM) using a Box-Behnken design demonstrated that the optimal conditions for the temperature, pH, inoculation dose of Alcaligenes sp. R3 and initial tetracycline concentration were 32.55 °C, 8.83, 17.32% and 54.58 mg/L, respectively. Alcaligenes sp. R3 could remove 71.62% of tetracycline at most. To improve the ability of Alcaligenes sp. R3 to remove tetracycline, it was immobilized with carboxymethylcellulose (CMC) and polydopamine (PDA) to construct immobilized microbe pellets (IMPs); scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) of the IMPs showed that the CMC/PDA exhibited good adsorption ability and biocompatibility and could thus be used as a carrier of the living cells. The maximum tetracycline removal percentage of the IMPs was 91.16%, indicating that the ability of the IMPs to remove tetracycline was superior to that of free cells. Through immobilization with CMC/PDA, IMPs could remove tetracycline more effectively and had better environmental tolerance than free Alcaligenes sp. R3. The identification of possible biodegradation products indicated that the degradation pathway of strain R3 was novel and CMC/PDA only adsorbed tetracycline but not have degradation effect on it. [Display omitted] •TTC degrading novel Alcaligenes strain R3 was isolated from swine manure.•The optimal degradation conditions of the TTC were evaluated by RSM.•A novel IMP was constructed to improve the ability of strain R3 to remove TTC.•Possible biodegradation pathways and products of TTC were proposed.